2020
DOI: 10.1002/ese3.653
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of temperature field in crack of supercritical carbon dioxide fracturing

Abstract: Supercritical carbon dioxide (SC-CO 2 ) fracturing technology has far-reaching application potential for unconventional resources which is beneficial to water protection and CO 2 sequestration. In this paper, temperature field in the crack of SC-CO 2 fracturing which will affect flow behavior of SC-CO 2 and the carrying capacity for proppants has been studied. A generalized and pragmatic numerical method coupled with the physical properties model of CO 2 and heat and mass transfer in the formation rock has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In addition, the stress component of the traction–separation model is also affected by the damage variable D during the failure of the CE according tot=1Dboldttrue¯,damageinitatedboldttrue¯,withoutdamagewhere t=tn,ts,tt refers to the nominal stress vector; boldttrue¯=tntrue¯,tstrue¯,tttrue¯ represents the stress components predicted by the elastic traction–separation behavior without damage for the current displacement. In this model, a bilinear cohesive law 43,44 is used to describe the relationship between traction force and displacement, as shown in Figure 2. In Equation (), dimensionless D represents the overall damage of the material cohesion unit during fracturing.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…In addition, the stress component of the traction–separation model is also affected by the damage variable D during the failure of the CE according tot=1Dboldttrue¯,damageinitatedboldttrue¯,withoutdamagewhere t=tn,ts,tt refers to the nominal stress vector; boldttrue¯=tntrue¯,tstrue¯,tttrue¯ represents the stress components predicted by the elastic traction–separation behavior without damage for the current displacement. In this model, a bilinear cohesive law 43,44 is used to describe the relationship between traction force and displacement, as shown in Figure 2. In Equation (), dimensionless D represents the overall damage of the material cohesion unit during fracturing.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…7 Therefore, one of the most urgent tasks in developing oil and gas fields is to "reduce cost and increase efficiency". 8 Proppant-crushing ratio and proppant fracture conductivity are two main indicators of proppant performance, 9,10 as well as being important parameters in proppant selection, 11,12 fracture design, 13,14 and postfracture evaluation. 15,16 Proppant-crushing ratio and fracture conductivity are generally tested by physical experiments, 15,[17][18][19] but physical experiments have limitations: long testing time, high cost, limited testing conditions, and significantly different results from repeated experiments under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical carbon dioxide (SC-CO 2 ) fracturing is regarded as a promising means in the development of unconventional oil and natural gas on account of its great advantages of environmental protection and resource-saving . CO 2 with specific pressures and temperatures is injected into the well and reaches the supercritical state (above 7.38 MPa and 304.1 K) at a certain position in the wellbore with the heat transfer with formation rocks, which could result in fracturing the formation and carry proppants into the fractures to form the flow channel of oil and natural gas from the reservoir to the well. , …”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies indicated that CO 2 fracturing fluid would turn into supercritical state under the effect of heat transfer with formation rock. SC-CO 2 has the advantages of better properties of diffusivity, solubility, flowability, and permeability and having less chemical additives, which make this technology a promising method to develop unconventional resources . However, some imperfections of SC-CO 2 fracturing were exposed in field applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation